Effects of axial motion and couple stress on lubrication performances of ship stern shaft. (June 2022) - Zheng, Liangyan; Zhu, Hanhua; Fan, Shidong; Yang, Taiwei; Wu, Jie; Wang, Chunping; Cao, Jiyin
Increasingly prominent marine oil pollution problems highlight the importance of environmentally friendly lubricants in a ship. According to the actual navigation environment, the couple stress effect of environmentally friendly lubricants and axial motion of stern shaft is considered to establish a new hydrodynamic lubrication model, and finite difference method and Simpson integral method have been utilized to solve film pressure and bearing carrying capacity, respectively. Various performance characteristics were obtained for a range of couple stress parameters, misalignment angles and rotation speeds. The results show that axial motion and couple stress have opposite effects on film distribution, the minimum film thickness decreases with the increasing of axial velocity while the maximum film pressure significant reduce as couple stress parameter grows. The axial position corresponding to the maximum pressure is reduced from 0.51 to 0.49 m as axial velocity enhances from 0 to 0.8 m/s while couple stress parameter is 0, but nearly remains the place while couple stress is considered. Meanwhile, couple stress lubricants effectively restrain friction of journal caused by hydrodynamic effect, and the decreasing amplitude is nearly independent of axial velocity.